A new subgenus and three new species of Sternoppia (Acari, Oribatida, Sternoppiidae) from Peru - Ermilov, Sergey G.; Subías, Luis S.; Shtanchaeva, Umukusum Ya.; Friedrich, Stefan (Zootaxa, 2022)
The oribatid mite family Sternoppiidae is recorded in Peru for the first time. A new subgenus and three new species of Sternoppia—Sternoppia (Andoppia) subgen. nov., S. (A.) tetratuberculata sp. nov., S. (Sternoppia) chinchaoensis sp. nov., and S. (S.) americaensis sp. nov.—are described, based on materials collected from upper soil and leaf litter in mountain forests in the Andes. Generic diagnosis, identification key, distribution and habitats of representatives of Sternoppia are presented.